2005
DOI: 10.1128/aem.71.5.2372-2380.2005
|View full text |Cite
|
Sign up to set email alerts
|

LuxS-Based Signaling Affects Streptococcus mutans Biofilm Formation

Abstract: Streptococcus mutans is implicated as a major etiological agent in human dental caries, and one of the important virulence properties of this organism is its ability to form biofilms (dental plaque) on tooth surfaces. We examined the role of autoinducer-2 (AI-2) on S. mutans biofilm formation by constructing a GS-5 luxS-null mutant. Biofilm formation by the luxS mutant in 0.5% sucrose defined medium was found to be markedly attenuated compared to the wild type. Scanning electron microscopy also revealed that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
175
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(183 citation statements)
references
References 57 publications
8
175
0
Order By: Relevance
“…Given that biofilm formation is regulated by AI-2 signalling in S. mutans [7,12,13], we decided to assess whether 20J extracts could interfere with biofilm formation of this early dental plaque colonizer. Indeed, the biofilm-inhibitory activity recorded in extracts of strain 20J suggested that it could be derived from the interference with the AI-2 QS system in S. mutans .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that biofilm formation is regulated by AI-2 signalling in S. mutans [7,12,13], we decided to assess whether 20J extracts could interfere with biofilm formation of this early dental plaque colonizer. Indeed, the biofilm-inhibitory activity recorded in extracts of strain 20J suggested that it could be derived from the interference with the AI-2 QS system in S. mutans .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Streptococcus species are the initial colonizers of clean teeth surfaces and the main components of early dental plaque. Although Streptococcus mutans was considered one of the major cariogenic bacteria in humans in the past [6,7], recent DNA- and RNA-based studies from carious lesions indicate that this bacterium represents only a small fraction of the bacterial community present in these lesions [8]. Biofilm formation by S. mutans is regulated by two QS systems, although the hierarchy of their organization is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gram-positive bacteria, and the AI-2 pathway can control the expression of genes involved in a variety of metabolic pathways and pathogenic mechanisms (25,43,44,45). Fries et al (46) showed that strains of F. nucleatum, P.…”
Section: Discussionmentioning
confidence: 99%